WORKSHOP PEMBUATAN MEDIA PEMBELAJARAN QUIS INTERAKTIF MENGGUNAKAN MICROSOFT POWERPOINT BAGI GURU SMPN 1 WAIGETE - Tanti Diyah Rahmawati; Nurfitriah Safrudin; Nur Chotimah; Fitriah Fitriah; Salwiana Salwiana (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
With the increasing development of technology, teachers are required to be able to master IT in learning. A variety of active and interactive learning media can motivate students in learning. This causes the need for interactive, fun, and easily accessible media. This service aims to provide knowledge and practice on making interactive learning media in the form of quizzes using PowerPoint. The results of this service got an excellent response from the teachers at SMPN 1 Waigete. With the resulting Quiz media in the form of PPT, the teachers felt that the media was beneficial and provided much knowledge that had not been obtained so far. It can be seen from the results of the questionnaire that mastery can make media quizzes using PPT 60%, while 40% still need guidance and assistance. Thus, the teachers feel that this service activity is significant to increasing their IT knowledge, and they hope that they will not stop making quizzes but can continue with other IT training because the teachers' mastery at SMPN 1 Waigete is still minimal